Case Study : Mamasab International Sdn Bhd / Muhammad Amirul Sharif - Sharif, Muhammad Amirul (2021)
This case study is important to assess the background of the founder and the company, the analysis of the company as well as the things that happen throughout the course of the business being run and the way the founders and the company solve problems. The case study was conducted with the purpose of research to find out more about who developed this Mamasab’s Bakery. This study wants to know more about the types of food sold by Mamasab’s Bakery and how marketing is carried out by the founders and the company. In this study, researchers can find out the types of strategies implemented by companies to gain consumer trust. Besides, the business nature of its founder plays a very important role in educating employees to cultivate noble values. Good entrepreneurial nature in business, it can give a good impact and provide benefits to the company as well as customers. The hard work done by Mamasab’s Bakery has made them famous for the products they sell other than other entrepreneurs. In this study the researcher used only secondary data obtained from internet sources. The researcher started this study after doing a web search that could be found on the relevant websites.